Biotropic : the journal of tropical biology - UIN Sunan Ampel Surabaya. Program Studi Biologi (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2017)
Articles on South East Asia tropical biology from various perspectives, covering both literary and fieldwork studies.
Keywords: Biology : Tropics : Periodicals; Biology; Tropics